Autophagy and mitochondrial biogenesis impairment contribute to age‐dependent liver injury in experimental sepsis: dysregulation of AMP‐activated protein kinase pathway. Issue 2 (4th January 2018) - Inata, Yu; Kikuchi, Satoshi; Samraj, Ravi S.; Hake, Paul W.; O'Connor, Michael; Ledford, John R.; O'Connor, James; Lahni, Patrick; Wolfe, Vivian; Piraino, Giovanna; Zingarelli, Basilia
Abstract : Age is an independent risk factor of multiple organ failure in patients with sepsis. However, the age‐related mechanisms of injury are not known. AMPK is a crucial regulator of energy homeostasis, which controls mitochondrial biogenesis by activation of peroxisome proliferator‐activated receptor‐γ coactivator‐α (PGC‐1α) and disposal of defective organelles by autophagy. We investigated whether AMPK dysregulation might contribute to age‐dependent liver injury in young (2–3 mo) and mature male mice (11–13 mo) subjected to sepsis. Liver damage was higher in mature mice than in young mice and was associated with impairment of hepatocyte mitochondrial function, structure, and biogenesis and reduced autophagy. At molecular analysis, there was a time‐dependent nuclear translocation of the active phosphorylated catalytic subunits AMPKα1/α2 and PGC‐1α in young, but not in mature, mice after sepsis. Treatment with the AMPK activator 5‐amino‐4‐imidazolecarboxamide riboside‐1‐β‐D‐ribofuranoside (AICAR) improved liver mitochondrial structure in both age groups compared with vehicle. In loss‐of‐function studies, young knockout mice with systemic deficiency of AMPKα1 exhibited greater liver injury than did wild‐type mice after sepsis. Our study suggests that AMPK is important for liver metabolic recovery during sepsis. Although its function may diminish with age, pharmacological activation of AMPK may be of therapeutic benefit.—Inata, Y., Kikuchi, S., Samraj, R. S., Hake, P. W., O'Connor, M., Ledford, J. R., O'Connor, J., Lahni, P., Wolfe, V., Piraino, G., Zingarelli, B. Autophagy and mitochondrial biogenesis impairment contribute to age‐dependent liver injury in experimental sepsis: dysregulation of AMP‐activated protein kinase pathway. FASEB J. 32, 728–741 (2018). www.fasebj.org